Combined Transcranial Direct Current Stimulation and Selective Motor Training Enhances Balance in Children With Autism Spectrum Disorder. Issue 1 (February 2020) - Mahmoodifar, Elham; Sotoodeh, Mohammad Saber
Previous studies have shown that transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) can facilitate the consolidation of motor skills in people who are typically developed, especially when tDCS is combined with goal-oriented exercises. Yet, the effect of tDCS on the motor skills of children with autism spectrum disorder is unknown. This study sought to investigate the effects of combined anodal tDCS and selective motor training on balance among 18 children with autism spectrum disorder (aged 6–14 years) who we randomly assigned to equal-sized experimental and control groups. The experimental group practiced motor training to improve balance after receiving 1.5 mA anodal tDCS over the left M1 for 20 minutes before each of 10 motor training sessions. The control (sham) group underwent a similar protocol with identical motor training, but tDCS was only artificially administered to them. We evaluated participants' balance at baseline and after training. Data analysis showed that both anodal tDCS plus motor skill training and motor skill training with sham tDCS had significant positive impacts on balance, but tDCS participants who received both actual tDCS and motor skill training performed significantly better than those who received SHAM tDCS and motor skill training. These preliminary findings suggest that tDCS may enhance motor skill training for children with autism spectrum disorder, but replications with larger samples involving participants with varying levels of autistic symptoms and varied tDCS stimulation polarity are needed to affirm the practical use of this noninvasive brain stimulation.